(untitled) (Biological Sciences - PJSIR, 2011)
Seven pure compounds of the Galinsoga parviflora: ?-sitosterol (1); octacosanoic acid (2); ursolic acid (3); 4-hydroxybenzoic acid (4); 3,4-dihydroxybenzoic acid (5); gallic acid (6); ?-sitosterol’ 3-0-, ?-D glucopyranoside (7) and the plant crude extract fractions were assayed in the laboratory for their nematicidal properties against plant parasitic nematodes Meloidogyne incognita (root-knot) and Cephalobus litoralis in different concentrations after 24 and 48 h. It was observed that crude extract, hexane, chloroform, ethyl acetate, methanol fractions and compounds no 1, 3, 4, and 7 showed significant activity whereas compounds 2, 5 and 6 showed low order of mortality.